Drift and beaching patterns of sea otter carcasses and car tire dummies. Issue 4 (3rd May 2019) - Young, Colleen; Eguchi, Tomoharu; Ames, Jack A.; Staedler, Michelle; Hatfield, Brian B.; Harris, Mike; Golson‐Fisch, Emily A.
Abstract: Enumerating and examining marine animal carcasses is important for quantifying mortality rates and determining causes of mortality. Drifter experiments are one tool for estimating at‐sea mortality and determining factors affecting carcass drift, but they require validation to confirm drifters accurately replicate the drift characteristics of the species of interest. The goal of this study was to determine whether dummies constructed from car tires were appropriate substitutes for sea otter ( Enhydra lutris ) carcasses. We released 33 sets of targets (carcasses and dummies) in a one‐to‐one ratio on 15 randomly chosen dates between January 1995 and December 1996. They were telemetrically tracked until they beached or were no longer detected. Beaching rates were similar between carcasses (69.7%) and dummies (66.7%). Our results indicated that there was no statistical difference in the drifting pattern, as measured by distance traveled and location, between carcasses and dummies, and that cumulative wind speed, days since release, and release month were predictors of drift patterns. We concluded that dummies constructed from car tires do imitate sea otter carcasses and could be used to estimate at‐sea mortality of sea otters, or, if released during or after an oil spill, could be used to direct search efforts for carcasses.